Step
*
2
of Lemma
Taylor-series-converges-everywhere
.....antecedent..... 
1. a : ℝ
2. F : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x = y) 
⇒ (F[k;x] = F[k;y]))
4. infinite-deriv-seq((-∞, ∞);i,x.F[i;x])
5. ∀r:{r:ℝ| r0 ≤ r} . lim k→∞.r^k * (F[k + 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. m : ℕ+
7. [%4] : icompact([r(-m), r(m)])
8. t : {t:ℝ| r0 < t} 
9. [r(-m), r(m)] ⊆ (a - t, a + t) 
⊢ infinite-deriv-seq((a - t, a + t);i,x.F[i;x])
BY
{ RepeatFor 2 (ParallelOp 4) }
1
1. a : ℝ
2. F : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x = y) 
⇒ (F[k;x] = F[k;y]))
4. ∀i:ℕ. d(F[i;x])/dx = λx.F[i + 1;x] on (-∞, ∞)
5. ∀r:{r:ℝ| r0 ≤ r} . lim k→∞.r^k * (F[k + 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. m : ℕ+
7. [%4] : icompact([r(-m), r(m)])
8. t : {t:ℝ| r0 < t} 
9. [r(-m), r(m)] ⊆ (a - t, a + t) 
10. i : ℕ
11. d(F[i;x])/dx = λx.F[i + 1;x] on (-∞, ∞)
⊢ d(F[i;x])/dx = λx.F[i + 1;x] on (a - t, a + t)
Latex:
Latex:
.....antecedent..... 
1.  a  :  \mBbbR{}
2.  F  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}k:\mBbbN{}.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (F[k;x]  =  F[k;y]))
4.  infinite-deriv-seq((-\minfty{},  \minfty{});i,x.F[i;x])
5.  \mforall{}r:\{r:\mBbbR{}|  r0  \mleq{}  r\}  .  lim  k\mrightarrow{}\minfty{}.r\^{}k  *  (F[k  +  1;x]/r((k)!))  =  \mlambda{}x.r0  for  x  \mmember{}  (-\minfty{},  \minfty{})
6.  m  :  \mBbbN{}\msupplus{}
7.  [\%4]  :  icompact([r(-m),  r(m)])
8.  t  :  \{t:\mBbbR{}|  r0  <  t\} 
9.  [r(-m),  r(m)]  \msubseteq{}  (a  -  t,  a  +  t) 
\mvdash{}  infinite-deriv-seq((a  -  t,  a  +  t);i,x.F[i;x])
By
Latex:
RepeatFor  2  (ParallelOp  4)
Home
Index